BPJS EMPLOYMENT COMMUNICATION STRATEGY MEULABOH BRANCH OFFICE IN SOCIALIZING SOCIAL SECURITY PROGRAM - Tasyia Maulian Sari; Safrizal Safrizal (RADJA PUBLIKA, 2022)
The importance of a good communication strategy is applied so that the program runs in accordance with the company's vision and mission. The purpose of this research is to describe the form of communication strategy of BPJS Employment at the Meulaboh Branch in Disseminating the Social Security Program and to find out what are the supporting factors and inhibiting factors faced by BPJS Ketenagakerjaan in disseminating the Program . Social Security. The type of research used is descriptive qualitative research. This research uses a communication approach. The data collection method is through interviews and documentation. The results show that (1) the strategy used by BPJS Ketenagakerjaan in Disseminating the Social Security Program is by making materials related to the delivery of the program and then how our way of communicating, the benefits of the Social Security Program, registration procedures, as well as coordinating directly with the community leader or if socializing to the company coordination with company management regarding the Social Security Program Socialization, (2) Barriers faced by BPJS Employment namely Language, Technology and Lack of insight of participants in knowing the difference between BPJS Employment and BPJS Health. Based on the results of the research, suggestions that can be given are: (1) BPJS Employment of the meulaboh branch should further increase the quantity of socialization in order to increase public interest in using social security programs (2) officers who cannot speak Acehnese can be given training to make it easier for officers to communicate well to people who cannot speak Indonesian.